Electrochemical device and electronic device
By constructing high -efficiency electron and ion conductive networks in the negative pole plates of lithium ion batteries, and using porous collecting fluids and silicon -based materials to solve the problem of lithium ion consumption and expansion caused by silicon -based materials in lithium -ion batteries, improved the battery Energy density and cycle performance.
Patent Information
- Application Number
- CN202411375136.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-21
AI Technical Summary
The lithium ion consumes a large amount of lithium ions in the negative electrode material layer in the lithium ion battery during the first cycle, and the thickness expansion during the lithium embedding process is large, resulting in the degradation of the first Coulomb efficiency, discharge rate performance and circulation performance of the battery.
By constructing high -efficiency electronics and ionic conductive networks for silicon negative chips, porous collecting fluids and negative active materials (including silicon -based materials) are used to improve lithium embedded and lithium uniformity, and reduce the problem of lithium ion consumption and expansion.
The volume energy density of the electrochemical device, the first Kuron efficiency, the discharge multiplier performance, and the recking capacity maintenance rate were reduced, reducing the thickness expansion rate of the battery.
Smart Images

Figure CN119340449A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemistry, and in particular to an electrochemical device and an electronic device. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, high power, and long cycle life. They are widely used in consumer electronics, electric bicycles, and electric vehicles. As their application scope continues to expand, the requirements for the energy density and cycle performance of lithium-ion batteries continue to increase. The current common graphite materials for lithium-ion battery negative electrodes can no longer meet the requirements for energy density. Silicon-carbon and silicon-oxygen have high theoretical specific capacity and are ideal materials to replace graphite negative electrodes and improve the energy density of lithium-ion batteries.
[0003] However, for lithium-ion batteries containing silicon-based materials in the negative electrode material layer, the silicon-based materials consume a large amount of lithium ions in the first cycle and expand in thickness during the lithium insertion process, resulting in a decrease in the first coulombic efficiency, discharge rate performance and cycle performance of the lithium-ion battery. Summary of the invention
[0004] The purpose of the present application is to provide an electrochemical device and an electronic device, by constructing a good electronic and ion conductive network of a silicon negative electrode plate, so that the lithium insertion and removal paths of the silicon negative electrode are unobstructed, the lithium insertion and removal uniformity of the overall negative electrode plate are improved, the structural stability of the silicon material is improved, the lithium ion consumption during the charging and discharging process of the silicon material is reduced, the expansion problem of the silicon negative electrode material is improved, and the discharge rate performance, the first coulomb efficiency and the cycle performance of the electrochemical device are improved.
[0005] It should be noted that in the invention content of this application, lithium-ion batteries are used as an example of electrochemical devices to explain this application, but the electrochemical devices of this application are not limited to lithium-ion batteries. The specific technical solutions are as follows:
[0006] The first aspect of the present application provides an electrochemical device, which includes a negative electrode plate, the negative electrode plate includes a porous current collector and a negative electrode material located on at least one surface of the porous current collector and in the pores of the porous current collector; the negative electrode material includes a negative electrode active material, the negative electrode active material includes a silicon-based material, and based on the mass of the negative electrode plate, the mass percentage of silicon element in the silicon-based material is 9% to 27%, preferably 20% to 25%; the pore size Hv50 of the porous current collector is 7μm to 15μm, preferably 9μm to 12μm; the porosity of the porous current collector is 50% to 70%, preferably 53% to 57%; the pore size Hv50 of the porous current collector is greater than the particle size Dv50 of the silicon-based material. When the pore size Hv50 of the porous current collector and the porosity of the porous current collector are within the above range, and the pore size Hv50 of the porous current collector is greater than the particle size Dv50 of the silicon-based material, the negative electrode active material can be effectively embedded in the pores of the porous current collector and uniformly surround the porous current collector, thereby constructing an efficient electron / ion conductive network of the negative electrode plate, improving the lithium insertion uniformity and lithium removal uniformity of the negative electrode plate, improving the ionic conductivity of the negative electrode plate, reducing the membrane resistivity of the negative electrode plate, inhibiting the expansion of the negative electrode plate, and reducing the thickness expansion rate of the electrochemical device, thereby improving the volume energy density, first coulomb efficiency, discharge rate performance and cycle capacity retention rate of the electrochemical device; at the same time, when the mass percentage of silicon element in the silicon-based material is within the scope of this application, after the silicon-based material is embedded in the pores of the porous current collector, a part of it still exists on the surface of the porous current collector, so that the negative electrode plate has an efficient electronic conductive network, which effectively improves the volume energy density of the electrochemical device.
[0007] In one embodiment of the present application, the silicon-based material includes at least one of a silicon-carbon material or a silicon-oxygen material, and the Dv50 of the silicon-based material is 5 μm to 13 μm. When the Dv50 of the silicon-based material is within the above range, the silicon-based material has good processability, improves the rolling density and volume energy density of the negative electrode sheet, and improves the ionic conductivity of the negative electrode sheet. When the Dv50 of the silicon-based material is within the above range, the specific surface area of the silicon-based material is within a suitable range, which reduces the consumption of the electrolyte during the cycle, thereby improving the kinetic performance and cycle performance of the electrochemical device.
[0008] In one embodiment of the present application, the pore size Hv50 of the porous current collector and the Dv50 of the silicon-based material satisfy: 1μm≤Hv50-Dv50≤3μm. When the value of Hv50-Dv50 is within the above range, the silicon-based material can be effectively embedded in the pores of the porous current collector, and the silicon-based material is evenly distributed in the porous current collector, so as to achieve good contact between the negative electrode active material and the porous current collector, improve the uniformity of lithium insertion and lithium removal of the negative electrode sheet, thereby reducing the film resistivity of the negative electrode sheet, improving the ionic conductivity of the negative electrode sheet, inhibiting the thickness expansion during the cycle, and reducing the coating leakage during the process coating process, thereby improving the cycle performance and volume energy density of the electrochemical device.
[0009] In some embodiments of the present application, the negative electrode active material further includes graphite, and the mass percentage of the silicon-based material is 18.6% to 53%, preferably 40% to 45%, based on the mass of the negative electrode sheet; the mass percentage of the graphite is A%, and 0<A≤30 based on the mass of the negative electrode sheet. When the mass percentage of the silicon-based material and the mass percentage of the graphite are within the above ranges, the negative electrode sheet has a lower film resistivity, and at this time, the volume proportion of the porous current collector in the negative electrode sheet is within a suitable range, and the negative electrode sheet has good processability, which is beneficial to the improvement of the volume energy density of the electrochemical device.
[0010] In one embodiment of the present application, the negative electrode material includes an additive, and the additive includes at least one of polyethylene oxide, polydimethylsiloxane, polyacrylonitrile, polyacrylic acid, 1-propyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide salt, 1-hydroxyethyl-3-methylimidazolium tetrafluoroborate, 1-propyl-1-methylpiperidinium bis(trifluoromethanesulfonyl)imide salt, and the mass percentage of the additive is 0.1% to 2% based on the mass of the negative electrode material. When the additive is selected from the above substances and the mass percentage is within the scope of the present application, an electron channel and an ion channel can be constructed inside the negative electrode plate, the lithium insertion uniformity and lithium removal uniformity of the negative electrode plate are improved, and it is conducive to forming a stable solid electrolyte interface film (SEI film), enhancing the overall adhesion of the negative electrode material, and improving the kinetic performance of the negative electrode plate, thereby improving the cycle performance of the electrochemical device.
[0011] In one embodiment of the present application, the film resistivity of the negative electrode sheet is 0.1Ω×cm to 5Ω×cm. When the film resistivity of the negative electrode sheet is within the above range, the electron conduction of the negative electrode sheet is smooth, and the electrochemical device has a higher discharge rate, first coulomb efficiency and cycle performance.
[0012] In one embodiment of the present application, the ionic conductivity of the negative electrode sheet is 0.2S / cm to 0.4S / cm. When the ionic conductivity of the negative electrode sheet is within the above range, the ion conduction of the negative electrode sheet is smooth, and the electrochemical device has a high discharge rate, first coulomb efficiency and cycle performance.
[0013] The second aspect of the present application provides an electronic device, which includes the electrochemical device in any of the above embodiments. The electronic device of the present application can improve the expansion problem of silicon negative electrode materials, and improve the discharge rate performance, first coulomb efficiency and cycle performance of the electronic device.
[0014] Beneficial effects of this application:
[0015] The present application provides an electrochemical device and an electronic device, wherein the electrochemical device includes a negative electrode plate, the negative electrode plate includes a porous current collector and a negative electrode active material located on at least one surface of the porous current collector and in the pores of the porous current collector; the negative electrode active material includes a silicon-based material, and the mass percentage of silicon element in the silicon-based material is 9% to 27% based on the mass of the negative electrode plate; the pore size Hv50 of the porous current collector is 7μm to 15μm; the porosity of the porous current collector is 50% to 70%; the pore size Hv50 of the porous current collector is greater than the particle size Dv50 of the silicon-based material. When the pore size Hv50 of the porous current collector and the porosity of the porous current collector are within the above range, and the pore size Hv50 of the porous current collector is greater than the particle size Dv50 of the silicon-based material, the negative electrode active material can be effectively embedded in the pores of the porous current collector and uniformly surround the porous current collector to construct an efficient electron / ion conductive network of the negative electrode pole piece, improve the lithium insertion uniformity and lithium removal uniformity of the negative electrode pole piece, improve the ionic conductivity of the negative electrode pole piece, reduce the membrane resistivity of the negative electrode pole piece, inhibit the expansion of the negative electrode pole piece, reduce the thickness expansion rate of the electrochemical device, and thereby improve the volume energy density, first coulomb efficiency, discharge rate performance and cycle capacity retention rate of the electrochemical device; at the same time, when the mass percentage of silicon element in the silicon-based material is within the scope of this application, after the silicon-based material is embedded in the pores of the porous current collector, a part of it still exists on the surface of the porous current collector, so that the negative electrode pole piece has an efficient electronic conductive network, thereby improving the volume energy density of the electrochemical device.
[0016] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0018] Figure 1 This is an electron microscope scanning image of a porous current collector according to an embodiment of the present application at a magnification of 500 times;
[0019] Figure 2 This is an electron microscope scanning image of a cross section of the negative electrode sheet along the thickness direction in Example 1-1 of the present application at a magnification of 3000 times. DETAILED DESCRIPTION
[0020] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0021] It should be noted that in the specific embodiments of the present application, a lithium-ion battery is used as an example of an electrochemical device to explain the present application, but the electrochemical device of the present application is not limited to a lithium-ion battery.
[0022] The first aspect of the present application provides an electrochemical device, which includes a negative electrode plate, the negative electrode plate includes a porous current collector and a negative electrode material located on at least one surface of the porous current collector and in the pores of the porous current collector; the negative electrode material includes a negative electrode active material, the negative electrode active material includes a silicon-based material, and based on the mass of the negative electrode plate, the mass percentage of silicon element in the silicon-based material is 9% to 27%, preferably 20% to 25%; the pore size Hv50 of the porous current collector is 7μm to 15μm, preferably 9μm to 12μm; the porosity of the porous current collector is 50% to 70%, preferably 53% to 57%; the pore size Hv50 of the porous current collector is greater than the particle size Dv50 of the silicon-based material. For example, the mass percentage of silicon element in the silicon-based material can be 9%, 11%, 13%, 15%, 17%, 20%, 23%, 25%, 27% or a range consisting of any two of the values therein; the pore size Hv50 of the porous current collector can be 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 15μm or a range consisting of any two of the values therein; the porosity of the porous current collector can be 50%, 53%, 55%, 57%, 60%, 65%, 70% or a range consisting of any two of the values therein. Without being limited to any theory, the inventors of the present application have found that when the pore size Hv50 of the porous current collector and the porosity of the porous current collector are within the above range, and the pore size Hv50 of the porous current collector is greater than the particle size Dv50 of the silicon-based material, the negative electrode active material can be effectively embedded in the pores of the porous current collector, and can evenly surround the porous current collector to construct an efficient electron / ion conductive network of the negative electrode pole piece, improve the lithium insertion uniformity and lithium removal uniformity of the negative electrode pole piece, improve the ionic conductivity of the negative electrode pole piece, reduce the membrane resistivity of the negative electrode pole piece, inhibit the expansion of the negative electrode pole piece, reduce the thickness expansion rate of the electrochemical device, and thereby improve the volume energy density, first coulomb efficiency, discharge rate performance and cycle capacity retention rate of the electrochemical device; at the same time, when the mass percentage of silicon element in the silicon-based material is within the range of the present application, after the silicon-based material is embedded in the pores of the porous current collector, a part of it still exists on the surface of the porous current collector, so that the negative electrode pole piece has an efficient electronic conductive network, which effectively improves the volume energy density of the electrochemical device.
[0023] The schematic diagram of the structure of the porous current collector in this application is as follows Figure 1 shown.
[0024] In this application, Dv50 refers to the particle size that reaches 50% of the volume accumulation measured from the small particle size in the volume-based particle size distribution of the material; Hv50 refers to the pore size that reaches 50% of the volume accumulation measured from the small pore size in the volume-based pore size distribution of the material.
[0025] In one embodiment of the present application, the silicon-based material includes at least one of a silicon-carbon material or a silicon-oxygen material, and the Dv50 of the silicon-based material is 5μm to 13μm; preferably, the silicon-based material is a silicon-carbon material. For example, the Dv50 of the silicon-based material can be 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm or a range consisting of any two of the values. When the Dv50 of the silicon-based material is within the above range, the silicon-based material has good processability, improves the rolling density and volume energy density of the negative electrode sheet, and improves the ionic conductivity of the negative electrode sheet. When the Dv50 of the silicon-based material is within the above range, the specific surface area of the silicon-based material is within a suitable range, which reduces the consumption of the electrolyte during the cycle, thereby improving the kinetic performance and cycle performance of the electrochemical device.
[0026] In one embodiment of the present application, the pore size Hv50 of the porous current collector and the Dv50 of the silicon-based material satisfy: 1μm≤Hv50-Dv50≤3μm. For example, the value of Hv50-Dv50 can be 1μm, 1.5μm, 2μm, 2.5μm, 3μm or a range consisting of any two of these values. When the value of Hv50-Dv50 is within the above range, the silicon-based material can be effectively embedded in the pores of the porous current collector, and the silicon-based material is evenly distributed in the porous current collector, achieving good contact between the negative electrode active material and the porous current collector, improving the lithium insertion uniformity and lithium removal uniformity of the negative electrode sheet, thereby reducing the film resistivity of the negative electrode sheet, improving the ionic conductivity of the negative electrode sheet, inhibiting the thickness expansion during the cycle, and reducing the coating leakage during the process coating process, thereby improving the cycle performance and volume energy density of the electrochemical device.
[0027] In one embodiment of the present application, the negative electrode active material also includes graphite, and the mass percentage of the silicon-based material is 18.6% to 53%, preferably 40% to 45%, based on the mass of the negative electrode plate; the mass percentage of graphite is A%, 0<A≤30 based on the mass of the negative electrode plate. For example, the mass percentage of the silicon-based material can be 18.6%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 53% or a range consisting of any two values therein; the mass percentage A of graphite can be 0.1%, 5%, 10%, 15%, 20%, 25%, 30% or a range consisting of any two values therein. When the mass percentage of the silicon-based material and the mass percentage of the graphite are within the above range, the negative electrode plate has a lower film resistivity, at which time the volume proportion of the porous current collector in the negative electrode plate is within a suitable range, the negative electrode plate has good processability, and the volume energy density of the electrochemical device is high.
[0028] In one embodiment of the present application, the negative electrode material includes an additive, and the additive includes at least one of polyethylene oxide, polydimethylsiloxane, polyacrylonitrile, polyacrylic acid, 1-propyl-1-methylpyrrolidine bis trifluoromethanesulfonyl imide salt, 1-hydroxyethyl-3-methylimidazolium tetrafluoroborate, 1-propyl-1-methylpiperidinium bis trifluoromethanesulfonyl imide salt or tri-n-butylmethylammonium bis (trifluoromethanesulfonyl) imide salt, and the mass percentage of the additive is 0.1% to 2% based on the mass of the negative electrode material. For example, the mass percentage of the additive can be 0.1%, 0.2%, 0.5%, 1%, 1.5%, 2%, or a range consisting of any two of the values. When the additives are selected from the above substances and their mass percentage is within the scope of this application, electron channels and ion channels can be constructed inside the negative electrode plate, thereby improving the lithium insertion and removal uniformity of the negative electrode plate, which is conducive to the formation of a relatively stable solid electrolyte interface film (SEI film), enhancing the overall adhesion of the negative electrode material, and improving the kinetic performance of the negative electrode plate, thereby improving the cycle performance of the electrochemical device.
[0029] In one embodiment of the present application, the film resistivity of the negative electrode sheet is 0.1Ω×cm to 5Ω×cm. For example, the film resistivity of the negative electrode sheet can be 0.1Ω×cm, 0.5Ω×cm, 1Ω×cm, 1.5Ω×cm, 2Ω×cm, 2.5Ω×cm, 3Ω×cm, 3.5Ω×cm, 4Ω×cm, 4.5Ω×cm, 5Ω×cm, or a range consisting of any two values therein. When the film resistivity of the negative electrode sheet is within the above range, the electron conduction of the negative electrode sheet is smooth, and the electrochemical device has a higher discharge rate, first coulomb efficiency, and cycle performance.
[0030] In one embodiment of the present application, the ionic conductivity of the negative electrode sheet is 0.2S / cm to 0.4S / cm. For example, the ionic conductivity of the negative electrode sheet can be 0.2S / cm, 0.22S / cm, 0.24S / cm, 0.26S / cm, 0.28S / cm, 0.3S / cm, 0.32S / cm, 0.34S / cm, 0.36S / cm, 0.38S / cm, 0.4S / cm, or a range consisting of any two of these values. When the ionic conductivity of the negative electrode sheet is within the above range, the ion conduction of the negative electrode sheet is smooth, and the electrochemical device has a higher discharge rate, first coulomb efficiency, and cycle performance.
[0031] The present application has no particular limitation on the method for preparing the porous current collector. For example, the method for preparing the porous current collector may include but is not limited to obtaining the porous current collector by copper plating on a porous melt-blown non-woven fabric.
[0032] In the present application, the pore size Hv50 of the porous current collector can be controlled by adjusting the hot air pressure, hot air temperature and copper plating thickness of the non-woven fabric in the process of preparing the meltblown non-woven fabric. When the hot air pressure and temperature in the process of preparing the meltblown non-woven fabric increase, the pore size Hv50 of the porous current collector decreases; when the hot air pressure and temperature in the process of preparing the meltblown non-woven fabric decrease, the pore size Hv50 of the porous current collector increases; when the copper plating thickness of the non-woven fabric increases, the pore size Hv50 of the porous current collector decreases; when the copper plating thickness of the non-woven fabric decreases, the pore size Hv50 of the porous current collector increases.
[0033] In the present application, the porosity of the porous current collector can be regulated by adjusting the hot air pressure, hot air temperature and copper plating thickness of the non-woven fabric during the preparation of the melt-blown non-woven fabric. When the hot air pressure and hot air temperature increase during the preparation of the melt-blown non-woven fabric, the porosity of the porous current collector increases, and when the hot air pressure and hot air temperature decrease during the preparation of the melt-blown non-woven fabric, the porosity of the porous current collector decreases; when the copper plating thickness of the non-woven fabric decreases, the porosity of the porous current collector increases, and when the copper plating thickness of the non-woven fabric increases, the porosity of the porous current collector decreases.
[0034] In one embodiment of the present application, when the volume of the porous collector remains unchanged, the mass of the porous collector can be controlled by adjusting the porosity of the porous collector. The larger the porosity of the porous collector, the smaller the mass of the porous collector; the smaller the porosity of the porous collector, the greater the mass of the porous collector.
[0035] In one embodiment of the present application, based on the mass of the negative electrode plate, the mass percentage of silicon element can be controlled by adjusting the mass ratio of the negative electrode material and the porous current collector. The greater the added mass ratio of the negative electrode material and the porous current collector, the greater the mass percentage of silicon element; the smaller the mass ratio of the negative electrode material and the porous current collector, the smaller the mass percentage of silicon element.
[0036] In one embodiment of the present application, based on the mass of the negative electrode plate, the mass percentage of silicon element can be controlled by adjusting the mass ratio of silicon-based material and graphite. The larger the mass ratio of silicon-based material and graphite, the greater the mass percentage of silicon element; the smaller the mass ratio of silicon-based material and graphite, the smaller the mass percentage of silicon element.
[0037] In one embodiment of the present application, based on the mass of the negative electrode plate, the mass percentage of the silicon-based material can be controlled by adjusting the mass ratio of the negative electrode material and the porous current collector. The larger the mass ratio of the negative electrode material and the porous current collector, the larger the mass percentage of the silicon-based material; the smaller the mass ratio of the negative electrode material and the porous current collector, the smaller the mass percentage of the silicon-based material.
[0038] In one embodiment of the present application, based on the mass of the negative electrode plate, the mass percentage of the silicon-based material can be controlled by adjusting the mass ratio of the silicon-based material and graphite. The larger the mass ratio of the silicon-based material and graphite, the greater the mass percentage of the silicon-based material; the smaller the mass ratio of the silicon-based material and graphite, the smaller the mass percentage of the silicon-based material.
[0039] In the present application, the electrochemical device also includes a positive electrode plate, which includes a positive electrode collector and a positive electrode material layer disposed on at least one surface of the positive electrode collector. The above-mentioned "positive electrode material layer disposed on at least one surface of the positive electrode collector" means that the positive electrode material layer can be disposed on one surface of the positive electrode collector along its own thickness direction, or on two surfaces of the positive electrode collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the positive electrode collector, or it can be a partial area of the surface of the positive electrode collector. This application has no special restrictions, as long as the purpose of this application can be achieved.
[0040] The present application has no particular limitation on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).
[0041] The positive electrode material layer includes a positive electrode active material. The present application has no particular limitation on the positive electrode active material as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to lithium nickel cobalt manganese oxide (such as NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO 2 ), at least one of lithium manganese oxide, lithium iron manganese phosphate or lithium titanate.
[0042] The positive electrode material layer may also include a conductive agent and a binder. The present application does not particularly limit the types of conductive agents and binders, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of conductive carbon black (SuperP), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers, and the conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers, and specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. The binder may include, but is not limited to, at least one of sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber, or polyvinylidene fluoride.
[0043] The present application has no particular restriction on the mass ratio of the positive electrode active material, the conductive agent, and the binder in the positive electrode material layer. Those skilled in the art can select the ratio according to actual needs as long as the purpose of the present application can be achieved.
[0044] The present application has no particular limitation on the thickness of the positive electrode current collector and the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm, and the thickness of the positive electrode material layer is 30 μm to 120 μm.
[0045] Optionally, the positive electrode sheet may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The composition of the conductive layer is not particularly limited, and it can be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, for example, it can be at least one of the above conductive agent and the above binder.
[0046] In the present application, the electrochemical device also includes an isolation membrane. The present application has no particular restrictions on the isolation membrane, as long as the purpose of the present application can be achieved. For example, the material of the isolation membrane may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The type of isolation membrane may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.
[0047] In some embodiments of the present application, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.
[0048] Optionally, a surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.
[0049] In some embodiments of the present application, the inorganic layer includes inorganic particles and a binder. The present application is not particularly limited to inorganic particles, such as inorganic particles can include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application is not particularly limited to binder, such as binder can be at least one of the above-mentioned binders. In some embodiments of the present application, the polymer layer includes polymer, and the material of the polymer includes at least one of polyamide, acrylate polymer, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether or polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).
[0050] In the present application, the thickness of the isolation film is not particularly limited as long as the purpose of the present application can be achieved. For example, the thickness of the isolation film may be 3 μm to 30 μm.
[0051] In some embodiments of the present application, the negative electrode material may further include a conductive agent, a binder, and a dispersant. The present application does not particularly limit the types of the conductive agent and the binder, as long as the purpose of the present application can be achieved. For example, it may be at least one of the above conductive agent and the above binder. The present application does not particularly limit the type of the dispersant, as long as the purpose of the present application can be achieved. For example, the dispersant may include but is not limited to at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium polyacrylate, or lithium polyacrylate.
[0052] The present application has no particular limitation on the thickness of the porous current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the porous current collector is 4 μm to 33 μm.
[0053] In the present application, after the preparation of the negative electrode plate is completed, the negative electrode plate can also be supplemented with lithium, which can further improve the initial coulombic efficiency of the lithium-ion battery. The porous current collector structure of the negative electrode plate of the present application enables the negative electrode plate to have good lithium ion conductivity, which is beneficial to the uniformity of lithium removal and lithium insertion of the negative electrode plate, and can achieve a uniform distribution of lithium ions in the thickness direction of the negative electrode plate when supplementing lithium. The present application does not particularly limit the method of supplementing lithium for the negative electrode plate, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. For example, the method of supplementing lithium for the negative electrode plate may include but is not limited to at least one of lithium powder supplementation, lithium strip supplementation, or electrochemical lithium supplementation.
[0054] In the present application, the electrochemical device further includes an electrolyte, and the electrolyte includes a lithium salt and a non-aqueous solvent.
[0055] The present application has no particular restrictions on lithium salts, as long as the purpose of the present application can be achieved. For example, lithium salts may include but are not limited to LiPF 6 , LiBF 4 、LiAsF 6 、LiClO 4 、LiB(C 6 H 5 ) 4 、LiCH 3 SO 3 、LiCF 3 SO 3 、LiN(SO 2 CF 3 ) 2 、LiC(SO 2 CF 3 ) 3 , Li 2 SiF 6 At least one of lithium bis(oxalatoborate) (LiBOB) or lithium difluoroborate. The present application has no particular limitation on the content of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved.
[0056] The present application has no particular limitation on the non-aqueous solvent as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents.
[0057] The carbonate compound may include but is not limited to at least one of a linear carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The linear carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or methyl ethyl carbonate (MEC). The cyclic carbonate may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application has no particular restrictions on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved.
[0058] The electrochemical device also includes a housing for accommodating a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the field of electrochemical devices, and this application does not limit the above-mentioned other components. This application does not particularly limit the housing, and it can be a housing known in the art, as long as the purpose of this application can be achieved. For example, the housing can be a hard shell housing or a flexible shell. The material of the hard shell housing can be metal, and this application does not limit the type of metal, and a metal hard shell housing known in the art can be used, as long as the purpose of this application can be achieved. The flexible housing can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.
[0059] The preparation process of the electrochemical device of the present application is well known to those skilled in the art, and the present application has no particular limitations. For example, the preparation process of the electrochemical device may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly with a wound structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. Alternatively, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly with a stacked structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the shell as needed to prevent pressure rise and overcharge and discharge inside the electrochemical device.
[0060] A second aspect of the present application provides an electronic device, which includes the electrochemical device in any of the aforementioned embodiments.
[0061] The present application does not particularly limit the type of electronic device, and it can be used for any electronic device known in the prior art. In some embodiments of the present application, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0062] Example
[0063] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0064] Test methods and equipment:
[0065] Porous current collector Hv50 and porosity test
[0066] The Hv50 and porosity of the porous current collector were tested by mercury intrusion method (AutoPore IV 9600). A fully discharged (discharge condition: discharge at a constant current of 0.5C to a voltage of 2.5V) lithium-ion battery was taken, the negative electrode sheet was disassembled, the negative electrode material was washed off with dimethyl carbonate solvent, and then the solvent was washed off with deionized water, and dried to obtain a porous current collector. The current collector was cut into 2cm×20cm strips, and the weight of the strips was recorded as m 1 (sample weight), place the sample into the dilatometer, seal it, and then weigh it and record the weight as m 2 (sample weight + dilatometer weight), then fill with mercury, conduct low pressure test (0.5psia to 50psia), and test m after the low pressure test 3 (sample weight + dilatometer weight + mercury filling weight), and then conduct a high pressure test (14.7psia to 60000psia), and then clean the dilatometer to complete the test, where porosity = pore volume / sample volume, pore volume is the volume of mercury entering the electrode pore during the pressure increase process from low pressure to high pressure (0.5psia to 60000psia) (can be converted to mercury volume according to the amount of mercury entered and the density of mercury), that is, the pore volume, sample volume = capillary volume of dilatometer - ((m 3 -m 2 ) / ρ 汞 ) The Hv50 of a porous current collector is the pore size that reaches 50% of the volume accumulation, measured from the smallest pore size, in the volume-based pore size distribution of the porous current collector.
[0067] Scanning electron microscope test
[0068] Take the negative electrode sheet and the porous current collector, perform ion cutting on the negative electrode sheet along the thickness direction, use a scanning electron microscope of model ZEIS-SEM (Sigma-02-33), select a section with an area ≥ (1cm×1cm), adjust the magnification to 3000 times, and take photos within the range of 42.3μm×30μm. Then use a scanning electron microscope of model ZEIS-SEM (Sigma-02-33), select the surface of the porous current collector with an area ≥ (1cm×1cm), adjust the magnification to 500 times, and take photos within the range of 254μm×180μm.
[0069] Silicon-based material Dv50 test
[0070] The fully discharged lithium-ion battery (discharging condition: discharging at a constant current of 0.5C to a voltage of 2.5V) was disassembled to obtain the anode electrode, which was soaked in dimethyl carbonate solvent for 2 hours, dried at 60°C for 1 hour, and then protected by an inert atmosphere (Ar gas) at a heating rate of 5°C / min to 600°C, and then kept at a constant temperature for 2 hours to obtain the main material sample powder;
[0071] The laser particle size analyzer (MasterSizer 3000) was used for testing. First, the sample injection system was cleaned with water, the refractive index was selected as 1.8, the absorbance was selected as 1, the dispersant name was selected as water, the dispersant refractive index was selected as 1.333, and the analysis model was selected as general non-spherical. When the test background light intensity was <200 or the laser intensity was >70%, the sample was added until the shading degree was within the range of 8% to 12%, then the sample was stopped, and the shading degree was observed to remain stable for 30 seconds, and then the particle size distribution diagram was obtained by testing. The Dv50 of the silicon-based material is the particle size that reaches 50% of the volume accumulation from the small particle size in the volume-based particle size distribution of the silicon-based material.
[0072] Discharge percentage test
[0073] At 25°C, the lithium-ion battery is charged to 4.5V at 1C constant current, then charged to 0.05C at 4.5V constant voltage, then discharged to 2.5V at 0.5C constant current, and the discharge capacity at this time is tested and recorded as the 25°C discharge capacity. At 25°C, the lithium-ion battery is charged to 4.5V at 1C constant current, then charged to 0.05C at 4.5V constant voltage, then placed in a -20°C thermostat, left to stand for 2 hours, and then discharged to 2.5V at 0.5C constant current, and the discharge capacity at this time is tested and recorded as the -20°C discharge capacity. The discharge rate performance of the lithium-ion battery is characterized by the discharge percentage. The higher the discharge percentage, the better the discharge rate performance of the lithium-ion battery.
[0074] Discharge percentage = (-20°C discharge capacity / 25°C discharge capacity) × 100%.
[0075] Cycle capacity retention test
[0076] At 45°C, the lithium-ion battery is charged to 4.5V at a constant current of 1C, then charged to a current of 0.05C at a constant voltage of 4.5V, and then discharged to 2.5V at a constant current of 0.5C, which is recorded as the discharge capacity of the first cycle. The lithium-ion battery is cycled 500 times under the above conditions, and the discharge capacity after 500 cycles is recorded. The cycle capacity retention rate is used to characterize the cycle performance of the lithium-ion battery. The higher the cycle capacity retention rate, the better the cycle performance of the lithium-ion battery.
[0077] Cycle capacity retention rate = (discharge capacity after 500 cycles / discharge capacity at the first cycle) × 100%.
[0078] Negative electrode ion conductivity test
[0079] The lithium-ion battery was baked at 60℃ for 4h before use. The disassembled negative electrode sheet was cut into small pieces larger than the size of the die with ceramic scissors and placed on the die for punching. The size of the die was 23mm×35mm×2mm. The area A and thickness d of the punched negative electrode sheet were measured, and then the punched negative electrode sheet was made into a single-layer symmetrical battery; the symmetrical battery was placed in an electrochemical workstation to test EIS, with the frequency set at 0.5Hz to 200kHz and the perturbation voltage at 10mV; the ionic resistance Rion of the negative electrode sheet was calculated by the intersection of the two straight lines in the electrochemical impedance spectroscopy (EIS).
[0080] Negative electrode plate ion conductivity = Rion × A / d.
[0081] First coulombic efficiency test
[0082] At 80°C and 1.2MPa, charge the lithium-ion battery at 0.1C constant current for 1200s, then at 0.9C constant current for 2400s, then reduce the pressure to 0.6MPa, continue charging at 1C constant current to 4.5V, and charge at 4.5V constant voltage to current 0.05C, and record the capacity at this time as C 0 , then discharge at 0.5C constant current to 2.5V, record capacity as D 0 , first coulombic efficiency = D 0 / C 0 ×100%.
[0083] Negative electrode film resistivity test
[0084] Take the prepared negative electrode sheet, first test and record the thickness of the negative electrode sheet, then use Yuanneng Technology BER2500 diaphragm resistance meter to test, hold the pressure for 10s, pressure ≥ 0.4T, and input the thickness of the sheet. After testing 12 values, output the test report, and take the average of the 12 diaphragm resistivities to get the diaphragm resistivity of the negative electrode sheet.
[0085] Cyclic Thickness Expansion Test
[0086] Place a lithium-ion battery between two flat plates, press the upper plate downward, and when the pressure is 700g, the distance between the two plates measured is the thickness of the lithium-ion battery.
[0087] At 45°C, charge the lithium-ion battery at 1C constant current to 4.5V, then charge at 4.5V constant voltage to a current of 0.05C, measure the thickness of the lithium-ion battery, that is, the thickness of the lithium-ion battery when it is fully charged for the first time, then discharge the lithium-ion battery at 0.5C to 2.5V, and then perform 500 cycles according to the above charge and discharge cycle process to test the thickness of the lithium-ion battery. The expansion performance of the lithium-ion battery is characterized by the thickness expansion rate. The lower the thickness expansion rate, the better the expansion performance of the lithium-ion battery.
[0088] Cycle thickness expansion rate = (thickness of lithium-ion battery after 500 cycles / thickness of lithium-ion battery in the first cycle - 1) × 100%
[0089] Lithium-ion battery volume energy density test
[0090] At 25°C, charge the lithium-ion battery at a constant current of 1C to 4.5V, then charge at a constant voltage of 4.5V to a current of 0.05C, and then discharge at 0.5C to 2.5V. Record the capacity at this time as D. Measure the length, width and thickness of the lithium-ion battery at this time, and calculate the volume V of the lithium-ion battery. At the same time, the discharge voltage platform P of the lithium-ion battery can be obtained. The volume energy density of the lithium-ion battery is: VED=D×P / V, in units of Wh / L.
[0091] Example 1-1
[0092] <Preparation of positive electrode sheet>
[0093] The positive electrode active material LiCoO 2 , conductive agent Super P, and binder polyvinylidene fluoride are mixed in a mass ratio of 97.9:0.9:1.2, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 75wt%, and the positive electrode slurry is obtained after vacuum stirring. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and dried at 120°C to obtain a positive electrode sheet with a single-sided positive electrode material layer. The coating weight of the positive electrode material layer is 267.8mg / 1540mm 2 Then repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. After drying at 120°C, cold pressing, cutting and welding the tabs, a positive electrode sheet with a specification of 74mm×867mm is obtained for standby use.
[0094] <Preparation of negative electrode sheet>
[0095] Silicon carbon particles with a Dv50 of 8 μm, binder styrene-butadiene rubber, conductive agent carbon nanotubes, dispersant sodium carboxymethyl cellulose, and additive polyethylene oxide are mixed in a mass ratio of 0.89:0.08:0.01:0.012:0.008 to obtain negative electrode materials, deionized water is added as a solvent, and a slurry with a solid content of 40 wt% is prepared. After being stirred evenly with a vacuum mixer, negative electrode slurry is obtained. A porous current collector with a pore size Hv50 of 10 μm, a porosity of 55%, and a thickness of 27 μm is taken, and the negative electrode slurry is evenly coated on one surface of the porous current collector, and dried at 120°C to obtain a negative electrode sheet with a single-sided coating of negative electrode material. The coating weight of the negative electrode material is 53.4 mg / 1540 mm 2. Then repeat the above steps on the other surface of the porous current collector to obtain a negative electrode sheet coated with negative electrode materials on both sides. After drying at 120°C, cold pressing, cutting and welding the pole ears, a negative electrode sheet with a specification of 78mm×875mm is obtained for standby use. Among them, based on the mass of the negative electrode material, the mass percentage of the additive is 0.8%; based on the mass of the negative electrode sheet, the mass percentage of the silicon-carbon particles is 42.6%, and the mass percentage of the porous current collector is 52.1%.
[0096] <Preparation of Electrolyte>
[0097] In an environment where the water content is less than 10 ppm, dimethyl carbonate, diethyl carbonate, and ethylene carbonate are mixed in a mass ratio of 1:1:1 to obtain a base solvent, and then the electrolyte salt LiPF is added to the organic solvent. 6 , mix evenly to obtain an electrolyte. Based on the mass of the electrolyte, the lithium salt LiPF 6 The mass percentage of is 12.5%, and the rest is base solvent.
[0098] <Isolation film>
[0099] A porous polyethylene film with a thickness of 7 μm (provided by Celgard Company) was used as the separator.
[0100] <Preparation of lithium-ion batteries>
[0101] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the electrode assembly is wound. The electrode assembly is placed in an aluminum-plastic film packaging bag, and the water is removed at 80°C, and the prepared electrolyte is injected. After vacuum packaging, standing, formation, degassing, and trimming steps, a lithium-ion battery is obtained. Among them, the formation upper limit voltage is 4.5V, the formation temperature is 70°C, and the formation standing time is 2h.
[0102] Example 1-2 to Example 1-6
[0103] Except that the Dv50 of the silicon-based material, the porosity and Hv50 of the porous current collector are adjusted as shown in Table 1 in <Preparation of Negative Electrode Plate>, the mass of the porous current collector, the mass percentage of the porous current collector based on the negative electrode plate, the mass of the negative electrode active material, and the mass percentage of the negative electrode active material based on the negative electrode plate change accordingly, and the total mass of the negative electrode plate and the mass ratio of the components in the negative electrode material remain unchanged, the rest is the same as Example 1-1.
[0104] Example 1-7 to Example 1-8
[0105] Except that the Dv50 of the silicon-based material is adjusted as shown in Table 1 in <Preparation of Negative Electrode Plate> and the value of Hv50-Dv50 is changed accordingly, the rest is the same as Example 1.
[0106] Example 1-9 to Example 1-12
[0107] Except that in <Preparation of Negative Electrode Plate>, graphite is added when preparing the negative electrode material, and the mass percentage of the silicon-based material based on the negative electrode plate and the mass percentage of the graphite based on the negative electrode plate are adjusted according to Table 1, the rest is the same as Example 1-1.
[0108] Examples 1-13
[0109] Except that in <Preparation of Negative Electrode Plate>, graphite is added when preparing the negative electrode material, and the mass percentage of the silicon-based material based on the negative electrode plate and the mass percentage of the graphite based on the negative electrode plate are adjusted according to Table 1, the rest is the same as Example 1-6.
[0110] Example 1-14 to Example 1-16
[0111] Except that in <Preparation of Negative Electrode Plate>, the mass percentage of the additive based on the negative electrode material is adjusted according to Table 1, the mass percentage of the silicon-based material based on the negative electrode plate changes accordingly, and the mass of the porous current collector and the mass of the negative electrode material remain unchanged, the rest is the same as Example 1-1.
[0112] Examples 1-17
[0113] Except that the type of silicon-based material is replaced by silicon-oxygen material from silicon-carbon material in <Preparation of Negative Electrode Plate> and the mass percentage of silicon element based on the negative electrode plate is increased to 25.6%, the rest is the same as Example 1.
[0114] Examples 1-18
[0115] The process is the same as that of Example 1 except that the type of additive is replaced by tri-n-butylmethylammonium bis(trifluoromethanesulfonyl)imide salt instead of polyethylene oxide in the preparation of negative electrode sheet.
[0116] Examples 1-19
[0117] Except that the type of additive in <Preparation of Negative Electrode Plate> is replaced by polyacrylonitrile from polyethylene oxide, the rest is the same as Example 1.
[0118] Comparative Example 1
[0119] Except that a porous current collector with a porosity of 78% and a pore size Hv50 of 16 μm is used in <Preparation of Negative Electrode Plate>, the mass of the porous current collector, the mass percentage of the porous current collector based on the negative electrode plate, the mass of the negative electrode active material, the mass percentage of the negative electrode active material based on the negative electrode plate and the value of Hv50-Dv50 change accordingly, the rest is the same as Example 1.
[0120] Comparative Example 2
[0121] Except that a porous current collector with a porosity of 45% and a Hv50 of 5 μm is used in <Preparation of Negative Electrode Plate>, the mass of the porous current collector, the mass percentage of the porous current collector based on the negative electrode plate, the mass of the negative electrode active material, the mass percentage of the negative electrode active material based on the negative electrode plate and the value of Hv50-Dv50 change accordingly, the rest is the same as Example 1.
[0122] Comparative Example 3
[0123] Except for adjusting the mass ratio of silicon-based material and graphite in <Preparation of Negative Electrode Plate> so that the mass percentage of silicon-based material based on the negative electrode plate and the mass percentage of graphite based on the negative electrode plate are as shown in Table 1, the rest is the same as Example 1.
[0124] Comparative Example 4
[0125] Except that the Dv50 of the silicon-based material is adjusted as shown in Table 1 in <Preparation of Negative Electrode Plate> and the value of Hv50-Dv50 is changed accordingly, the rest is the same as Example 1.
[0126] The preparation parameters and performance tests of each embodiment and comparative example are shown in Table 1.
[0127]
[0128]
[0129] It can be seen from Examples 1-1 to 1-8, Examples 1-17 and Comparative Examples 1 to 4 that when the pore size Hv50 and porosity of the porous current collector, the mass percentage of silicon element based on the negative electrode sheet, the type and particle size Dv50 of the silicon-based material, the mass percentage of the silicon-based material based on the negative electrode sheet, and the value of Hv50-Dv50 are within the scope of the present application, the membrane resistivity of the negative electrode sheet is low and the ion conductivity is high; since the porous current collector structure has good conductivity, the negative electrode active material can be effectively embedded in the pores of the porous current collector and can uniformly surround the porous current collector to construct an efficient electron / ion conductive network of the negative electrode sheet, improve the lithium de-lithiation uniformity and lithium insertion uniformity of the negative electrode sheet, and the obtained lithium ion battery has higher volume energy density, first coulomb efficiency, discharge percentage and cycle capacity retention rate, and lower thickness expansion rate. The pore size Hv50 and porosity of the porous current collector in Comparative Example 1 are greater than the scope of this application, and there is a lot of material leakage during the preparation of the negative electrode sheet. The negative electrode active material cannot be effectively embedded in the pores of the porous current collector, and the obtained lithium ion battery volume energy density, first coulomb efficiency, discharge percentage and cycle capacity retention rate are low, and the thickness expansion rate is high. The pore size Hv50 and porosity of the porous current collector in Comparative Example 2 are less than the scope of this application, and the Dv50 of the negative electrode active material is greater than the pore size Hv50 of the porous current collector. At this time, the negative electrode active material cannot be effectively embedded in the pores of the porous current collector, and the negative electrode active material accumulates on the surface of the porous current collector. The film resistivity of the negative electrode sheet is high and the ion conductivity is low. The volume energy density, first coulomb efficiency, discharge percentage and cycle capacity retention rate of the obtained lithium ion battery are low, and the thickness expansion rate is high. The mass percentage of silicon element in Comparative Example 3 is not within the scope of this application, and the obtained lithium ion battery volume energy density, first coulomb efficiency, discharge percentage and cycle capacity retention rate are low, and the thickness expansion rate is high. The value of Hv50-Dv50 in Comparative Example 4 is not within the scope of this application, and the obtained lithium-ion battery has low volume energy density, first coulomb efficiency, discharge percentage and cycle capacity retention rate, and high thickness expansion rate. It should be noted that when the mass of the negative electrode plate remains unchanged, the volume of the porous current collector remains unchanged, and silicon-carbon particles are used as silicon-based materials, the mass percentage of silicon element based on the negative electrode plate in Examples 1-6 has reached the theoretical maximum value, so there is no comparative example in which the mass percentage of silicon element based on the negative electrode plate exceeds the scope of this application.
[0130] Specifically, Figure 2 This is a scanning electron microscope image of a section along the thickness direction of the negative electrode sheet prepared in Example 1-1 at a magnification of 3000 times. It can be seen from the image that the negative electrode active material is effectively embedded in the pores of the porous current collector.
[0131] The mass percentage of graphite based on the negative electrode sheet usually affects the volume energy density, discharge rate performance, cycle performance and expansion performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-9 to 1-13 that when the mass percentage of graphite based on the negative electrode sheet is within the range of this application, the film resistivity of the negative electrode sheet is low, the ion conductivity is improved, and the volume proportion of the porous current collector in the negative electrode sheet is within a suitable range. The negative electrode sheet has good processability, and the obtained lithium-ion battery has a high volume energy density, first coulomb efficiency, discharge percentage and cycle capacity retention rate, and the thickness expansion rate is low.
[0132] The type of additives and the mass percentage of the additives based on the negative electrode sheet usually affect the volume energy density, discharge rate performance, cycle performance and expansion performance of the lithium-ion battery. It can be seen from Example 1-1, Example 1-18 to Example 1-19, and Example 1-14 to Example 1-16 that when the type and mass percentage of the additives are within the scope of this application, electron channels and ion channels can be constructed inside the negative electrode sheet, improving the uniformity of lithium removal and lithium insertion of the negative electrode sheet, which is conducive to the formation of a relatively stable solid electrolyte interface film (SEI film), which is beneficial to the overall adhesion and kinetic properties of the negative electrode material. As a result, the film resistivity of the negative electrode sheet is low and the ion conductivity is high, and the obtained lithium-ion battery has a higher volume energy density, first coulomb efficiency, discharge percentage and cycle capacity retention rate, and the thickness expansion rate is low.
[0133] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
[0134] It should be noted that, in this article, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article that includes a series of elements includes not only those elements, but also includes other elements that are not explicitly listed, or also includes elements that are inherent to such process, method or article.
[0135] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
Claims
1. An electrochemical device, comprising a negative electrode plate, the negative electrode plate comprising a porous current collector and a negative electrode material located on at least one surface of the porous current collector and in the pores of the porous current collector; the negative electrode material comprises a negative electrode active material, the negative electrode active material comprises a silicon-based material, and based on the mass of the negative electrode plate, the mass percentage of silicon element in the silicon-based material is 9% to 27%; the pore size Hv50 of the porous current collector is 7μm to 15μm, and the porosity of the porous current collector is 50% to 70%; the pore size Hv50 of the porous current collector is greater than the particle size Dv50 of the silicon-based material.
2. The electrochemical device according to claim 1, wherein: The pore size Hv50 of the porous current collector is 9 μm to 12 μm, and the porosity of the porous current collector is 53% to 57%.
3. The electrochemical device according to claim 1, wherein Based on the mass of the negative electrode plate, the mass percentage of the silicon element is 20% to 25%.
4. The electrochemical device according to claim 1, wherein The silicon-based material includes at least one of a silicon-carbon material or a silicon-oxygen material, and a Dv50 of the silicon-based material is 5 μm to 13 μm.
5. The electrochemical device according to claim 4, wherein: The pore size Hv50 of the porous current collector and the Dv50 of the silicon-based material satisfy: 1 μm≤Hv50-Dv50≤3 μm.
6. The electrochemical device according to claim 1, wherein The negative electrode active material further includes graphite. Based on the mass of the negative electrode plate, the mass percentage of the silicon-based material is 18.6% to 53%, and the mass percentage of the graphite is A%, 0<A≤30.
7. The electrochemical device according to claim 6, wherein: Based on the mass of the negative electrode plate, the mass percentage of the silicon-based material is 40% to 45%.
8. The electrochemical device according to claim 1, wherein The negative electrode material includes an additive, and the additive includes at least one of polyethylene oxide, polydimethylsiloxane, polyacrylonitrile, polyacrylic acid, 1-propyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide, 1-hydroxyethyl-3-methylimidazolium tetrafluoroborate, 1-propyl-1-methylpiperidinium bis(trifluoromethanesulfonyl)imide or tri-n-butylmethylammonium bis(trifluoromethanesulfonyl)imide. Based on the mass of the negative electrode material, the mass percentage of the additive is 0.1% to 2%.
9. The electrochemical device according to claim 1, wherein: The film resistivity of the negative electrode plate is 0.1Ω×cm to 5Ω×cm.
10. The electrochemical device according to claim 1, wherein The ionic conductivity of the negative electrode plate is 0.2S / cm to 0.4S / cm.
11. An electronic device comprising the electrochemical device according to any one of claims 1 to 10.
Citation Information
Cited By
Polyimide fiber-based composite gel electrolyte as well as preparation method and application thereof
CN121484189A
A polyimide fiber-based composite gel electrolyte, its preparation method and application
CN121484189B